2020
DOI: 10.3389/fimmu.2020.00462
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis Poly-γ-D-Glutamate Capsule Inhibits Opsonic Phagocytosis by Impeding Complement Activation

Abstract: Bacillus anthracis poly-γ-D-glutamic acid (PGA) capsule is an essential virulent factor that helps the bacterial pathogen to escape host immunity. Like other encapsulated bacterial species, the B. anthracis capsule may also inhibit complement-mediated clearance and ensure bacterial survival in the host. Previous reports suggest that B. anthracis spore proteins inhibit complement activation. However, the mechanism through which the B. anthracis capsule imparts a survival advantage to the active bacteria has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
0
21
0
5
Order By: Relevance
“…However, it can be generally agreed that its value has limitations when modelling disease ( 40 ). The capsule is known to protect extracellular bacteria from phagocytosis ( 14 , 41 ), and thus should be considered when modelling the extracellular dynamics of anthrax infection, which has not been explicitly modelled here. It is possible that the capsule also plays a role in protecting emerging intracellular bacteria from the antimicrobial environment of the host cell, since germinating spores are able to quickly produce and coat themselves in the capsule ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be generally agreed that its value has limitations when modelling disease ( 40 ). The capsule is known to protect extracellular bacteria from phagocytosis ( 14 , 41 ), and thus should be considered when modelling the extracellular dynamics of anthrax infection, which has not been explicitly modelled here. It is possible that the capsule also plays a role in protecting emerging intracellular bacteria from the antimicrobial environment of the host cell, since germinating spores are able to quickly produce and coat themselves in the capsule ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the anthrax toxins cause suppression of the host’s immune system, often leading to death of the host. Another important factor for the survival of B. anthracis bacteria in the host is the antiphagocytic capsule, which allows extracellular, vegetative bacteria to avoid eradication by the immune system by preventing the bacteria being phagocytosed and destroyed ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Образование компонентов капсулы кодирует плазмида pXO2. В результате возбудитель становится неуязвимым для иммунной системы хозяина (37,38). Токсины сибирской язвы представляют собой три белка, кодируемые плазмидой pXO1, -протективный антиген (PA), летальный фактор (LF) и отечный фактор (EF), которые объединяются в бинарные комплексы PA/LF и PA/EF с образованием соответственно летального токсина (LT) и отечного токсина (ET) (39).…”
Section: ключевые слова: сибирская язва Bacillus Anthracis ветеринарные вакцины рекомбинантные антигеныunclassified
“…This study demonstrated that encapsulated virulent strain exhibit resistance toward complement-dependent and complement-independent bacterial phagocytosis by human macrophages. After incubation with normal human serum or heat-inactivated serum as well as serum-free media, the non-encapsulated strain became highly susceptible to phagocytosis by THP-1 macrophages [174]. In particular, an increased deposition of the derivate b of the complement component 3 (C3b) that serves as a potent opsonizing agent, was observed at the surface of cells lacking their capsule.…”
Section: The Invisibility Cloak: the Capsulementioning
confidence: 99%